PENGARUH KEADILAN ORGANISASIONAL DAN PEMBERDAYAAN TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN PT. UNITED OVERSEAS BANK INDONESIA DI KOTA DENPASAR - Satya Pramudimas, Gede Oka; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
The purpose of the researcher wanted to know in this research is to test the influence of organizational justice at PT. United Overseas Bank, and test empowerment at PT. United Overseas Bank. This research was conducted on employees of PT. United Overseas Bank in Denpasar City. The sample of this research is 74 respondents with saturated sampling method. In this study data collection was done by distributing questionnaires and distributing questionnaires. The technique used in this research is multiple linear regression. The results of this study indicate that the variables of organizational justice and empowerment have a positive effect on organizational commitment of PT. United Overseas Bank in Denpasar City Keywords : organizational justice e, empowerment , training, organizational commitment